2018
DOI: 10.1177/2040620718780370
|View full text |Cite
|
Sign up to set email alerts
|

A case series of Kimura’s disease: a diagnostic challenge

Abstract: Kimura's disease (KD) is a rare, benign disorder characterized by subcutaneous masses with regional lymph-node enlargement. It is considered to be due to chronic inflammation of unclear etiology. Most cases have been reported in young, 20-30-year-old men of Asian descent. The diagnosis of KD is based on pathological features and elevated immunoglobulin E levels. Characteristic pathological features include intact lymph-node architecture, florid germinal center hyperplasia, extensive eosinophilic infiltrates, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 22 publications
0
42
0
2
Order By: Relevance
“…6 It was first described by Kimm and Szeto in China as eosinophilic hyperplastic lymphogranuloma. 6 Kimura et al from Japan reported a similar finding and described it as an "unusual granulation and hyperplastic changes of lymphatic tissue", and this condition has since become widely known as Kimura's disease. It is an uncommon disease in India with more preponderance to far eastern countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6 It was first described by Kimm and Szeto in China as eosinophilic hyperplastic lymphogranuloma. 6 Kimura et al from Japan reported a similar finding and described it as an "unusual granulation and hyperplastic changes of lymphatic tissue", and this condition has since become widely known as Kimura's disease. It is an uncommon disease in India with more preponderance to far eastern countries.…”
Section: Discussionmentioning
confidence: 99%
“…There are about 200 reported cases worldwide. 6,7 It is a benign inflammatory disease mostly affecting the head and neck region. 8 It usually involves the subcutaneous tissue, lymph nodes and the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations